Geriatric Nutritional Risk Index Predicts Adverse Outcomes in Human Malignancy: A Meta-Analysis. (19th November 2019) - Lv, Guo-yue; An, Lin; Sun, Da-wei
Abstract : Background. Geriatric Nutritional Risk Index (GNRI) has been widely used to assess the nutritional status in a variety of human pathological conditions, but the prognostic value of the GNRI in malignancies has not been evinced. Methods. Relevant studies updated on Jul 27, 2019, were retrieved in available databases, including PubMed, Web of Science, Cochrane library, Chinese CNKI, and Chinese Wan-fang. Hazard ratios (HRs) and 95% confidence intervals (CIs) were extracted and pooled by using STATA 14. Results. A total of 15 studies involving 8, 046 subjects were included in this meta-analysis. Meta-analysis results evinced that low GNRI was associated with poor OS (HR = 1.95, 95% CI: 1.49-2.56, p ≤ 0.001 ), poor CSS (HR = 1.81, 95% CI: 1.49-2.19, p ≤ 0.001 ), poor DFS (HR = 1.67, 95% CI: 1.28-2.17, p ≤ 0.001 ), and poor PFS (HR = 1.68, 95% CI: 1.28-2.21, p ≤ 0.001 ), and the correlation of GNRI with OS was not changed when stratified by possible confounding factors, suggesting that malignancy patients with low GNRI would suffer from reduced survival rate and increased recurrence rate. Moreover, low GNRI was also associated with postoperative complications in malignancies. Conclusions. In summary, GNRI is associated poor prognosis in human malignancies, and GNRI should be used as a predictive indicator of adverse outcomes during malignancy treatment.